GOLDEN AGE : METODE PEMBELAJARAN YANG TEPAT DAN ALAT PERAGA EDUKATIF (APE) UNTUK MENDORONG KUALITAS ANAK USIA EMAS PAUD DAN TK “HARAPAN” DI DUSUN BAJULMATI DESA GAJAHREJO KEC. GEDANGAN KABUPATEN MALANG - Enggar Nursasi; Siti Munfaqiroh (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
Activities that support the development of children in the golden age (1-5 years) can be done both at home and in PAUD and TK schools. Child growth at this time is fast. If the child can do the task given according to his age, then the chances of his success in carrying out other tasks according to the child's age development in the following year will be greater. The media used in children's cognitive development in early childhood and kindergarten is basically a safe and enjoyable medium. The teacher can use the media as an intermediary in delivering. An activity favored by PAUD and TK children is playing activities. Almost all playing activities actually use educational games (APE). "Harapan" PAUD and TK in Bajulmati village, Kec. Gedangan Malang Regency is in a very remote area and far from urban development. All-improper conditions cause the learning process to run simply. Limited facilities in the learning process cause the results of students are not optimal. The learning method applied by the teaching teacher is also still with old knowledge, not yet using the latest learning methods according to the development of the modern era education. The learning process will be more increased, interesting and the child will get the opportunity to develop all the potential that exists, the child will find himself, namely strengths, weaknesses, abilities and interests, even his own needs. So that it can improve cognitive development in children through learning strategies with game media in early childhood. Activities that have been carried out in the Community Partnership Program have been carried out to increase outdoor educational game equipment in the form of rocking and rocking bridges, as well as indoor educational games in the form of letters and numbers, lego puzzle pipes, pyramid, magic sand, color beams, puzlle beams , stamps, and equipped with lockers for storing student bags, as well as assistance with tambourine music equipment to balance right and left brain functions.